2023
DOI: 10.1038/s43247-022-00667-4
|View full text |Cite
|
Sign up to set email alerts
|

A generic hierarchical model of organic matter degradation and preservation in aquatic systems

Abstract: Organic matter degradation and preservation are crucial components of Earth’s carbon cycle. Empirical and phenomenological models usually contain parameters determined by site-specific data and focus on different aspects of the decay and accretion characteristics. To investigate more fundamental mechanisms, this study suggests a hierarchical model that links microscopic physical quantities to macroscopic degradation and preservation patterns. This mechanistic model predicts several commonly observed phenomena,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
(209 reference statements)
0
12
0
Order By: Relevance
“…This study has not included multiple limiting factors (e.g., OM quality, NO 3concentration) in N-cycling, as well as the complexity of pathways of denitrification, including directly denitrifying NO 3in overlying water and coupling of nitrification and denitrification processes at an oxic-anoxic sediment interface . MP as synthetic polymers potentially participates in OM degradation (Shang, 2023), and some materials (PLA) can serve as carbon sources which stimulate both nitrification and denitrification rates (Seeley et al, 2020). In a eutrophic system, OM (quality and quantity) constrains denitrification when overlying water provides sufficient NO 3 -; in a low-nutrient system, the NO 3supply from nitrification is the limiting factor for denitrification in the sediment .…”
Section: Discussion Bioturbation Coefficients In Mp-contaminated Systemmentioning
confidence: 99%
“…This study has not included multiple limiting factors (e.g., OM quality, NO 3concentration) in N-cycling, as well as the complexity of pathways of denitrification, including directly denitrifying NO 3in overlying water and coupling of nitrification and denitrification processes at an oxic-anoxic sediment interface . MP as synthetic polymers potentially participates in OM degradation (Shang, 2023), and some materials (PLA) can serve as carbon sources which stimulate both nitrification and denitrification rates (Seeley et al, 2020). In a eutrophic system, OM (quality and quantity) constrains denitrification when overlying water provides sufficient NO 3 -; in a low-nutrient system, the NO 3supply from nitrification is the limiting factor for denitrification in the sediment .…”
Section: Discussion Bioturbation Coefficients In Mp-contaminated Systemmentioning
confidence: 99%
“…A compilation of OC burial efficiencies suggests that sediments deposited in oxic bottom waters can have OC burial efficiencies that are 10 s of per cent lower than sediments deposited in anoxic bottom waters and that the difference becomes negligible at sedimentation rates above 200 g m −2 yr −1 [4,7]. A lower OC burial efficiency with increased O 2 exposure is supported by both field observations [6] and theoretical arguments [8]. Experimental studies have demonstrated that some fractions of organic matter are degraded less efficiently under anoxic conditions [911].…”
Section: Introductionmentioning
confidence: 89%
“…Such stochasticity emerges due to uncoordinated variations in generation or conversion rates, as well as nonselective transportation . When deterministic processes are spatiotemporally inconsistent or insufficient to overcome random effects like hydrologic mixing, stochasticity prevails in DOM molecular dynamics. , Considering the inherent stochastic nature of molecular dynamics, it is necessary to incorporate stochasticity into the mechanistic comprehension of the spatiotemporal variability of organic matter. , …”
Section: Introductionmentioning
confidence: 99%
“…17,18 Considering the inherent stochastic nature of molecular dynamics, it is necessary to incorporate stochasticity into the mechanistic comprehension of the spatiotemporal variability of organic matter. 19,20 The interplay between deterministic and stochastic factors in shaping DOM molecular assemblages bears resemblance to ecological processes in the microbial community assembly. 5 This thus offers an opportunity to employ ecological principles for a deeper understanding of DOM molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%